Association Between Prior Calcium Channel Blocker Use and Mortality in Septic Patients: A Meta-Analysis of Cohort Studies - Ding, Xianfei; Cui, Yuqing; Liang, Huoyan; Wang, Dong; Li, Lifeng; Kan, Quancheng; Wang, Lexin; Sun, Tongwen (Frontiers in Pharmacology, 2021)
Background: The aim of this study was to comprehensively review the literature and synthesize the evidence concerning the relationship between prior calcium channel blocker (CCB) use and mortality in patients with sepsis. Methods: The MEDLINE, EMBASE, Cochrane CENTRAL, and Web of Science databases were searched from their inception to April 9, 2020. Cohort studies related to prior CCB use in patients with sepsis were analysed. Pairs of reviewers independently screened the studies, extracted the data, and assessed the risk of bias. The primary outcome of 90-day mortality or secondary outcome of short-term mortality, including 30-day, ICU, and in-hospital mortality, were analysed. Heterogeneity among studies was assessed using the I2 statistic and was considered moderate if I2 was 50–75% and high if I2 was≥ 75%. Random-effects models were used to calculate the pooled odds ratios (ORs) and 95% confidence intervals (CIs). The quality of the studies was evaluated with the Newcastle-Ottawa Scale (NOS). Sensitivity analyses were performed to examine the robustness of the results. Results: In total, 639 potentially relevant studies were identified, and the full texts of 25 articles were reviewed. Ultimately, five cohort studies involving 280,982 patients were confirmed to have a low risk of bias and were included. Prior CCB use was associated with a significantly lower 90-day mortality in sepsis patients (OR, 0.90 [0.85-0.95]; I2 = 31.9%). Moreover, prior CCB use was associated with a significantly reduced short-term mortality rate in septic shock patients (OR, 0.61 [0.38-0.97]; I2 = 62.4%) but not in sepsis patients (OR, 0.83 [0.66-1.04]; I2 = 95.4%). Conclusions: This meta-analysis suggests that prior CCB use is significantly associated with improved 90-day mortality in sepsis patients and short-term mortality in septic shock patients. This study provides preliminary evidence of an association between prior CCB use and mortality in sepsis patients.